WARNA BUDAYA JAWA DALAM CERPEN “MACAN LAPAR” KARYA DANARTO - Yosi Wulandari; Muhammad Alfian Hermawan (Kantor Bahasa Provinsi Maluku Utara, 2021)
The use of a short storytelling style requires the author's expertise to play on the use of specific languages and certain styles. Likewise with danarto, in the short story